Implementation of Digital Entrepreneurship (DE) Program in Improving Entrepreneurship Competence Students of the University of 17 Agustus 1945 Banyuwangi - Oktavima Wisdaningrum (Jurnal Ilmu Manajemen Advantage, 2022)
Based on the results of the situation analysis that has been done, some students who take entrepreneurship courses feel that the concept of theory and application of entrepreneurship is not enough to compete in the current era. Increasing entrepreneurial competence through the Digital Entrepreneurship Program is an alternative solution to overcome these problems. The method used a descriptive qualitative approach. The variables in this study were Student Entrepreneurial Competence and the implementation of the Digital Entrepreneurship Program. The research results from the observation category related to the cognitive, affective, and psychomotor competencies of students in the field of entrepreneurship include; student abilities related to Online Store and Promotion Business by 30%, Community-Based Business by 20%, Content-Based Business and Matchmaking Business by 10%, Data Analysis by 45%, Cybersecurity by 35%, Cloud Computing by 15%, and Artificial Intelligence is 5%, Communication-customer services is 60%, Communication-customer services is 60% and Communication-customer complains is 40%. The results of the implementation of the Digital Entrepreneurship program related to increasing entrepreneurial competence in students are one of the recommendations of various parties in providing services for students who have businesses to improve their competencies so that their businesses can compete locally and globally.